2017
DOI: 10.1021/acs.langmuir.7b02925
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Salt-Controlled Self-Assembly of Triblock Copolymers F68 on Interaction Forces between Oil Drops in Aqueous Solution

Abstract: Nonionic triblock copolymers, surfactant Pluronic F68 (PEO76-PPO29-PEO76), are widely used in industrial processes, such as foaming, emulsification, and stabilization. The behaviors of triblock copolymers such as the salt-dependent self-assembly in bulk solution and the irreversible adsorption at the oil/water interface are mainly focused to explore their effects on the interaction forces between nano-spacing interfaces of oil droplets. In this study, the atomic force microscopy (AFM) technique was employed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…However, from the topographic images acquired by AFM surface imaging, it was found that the granular sensation of the surface is enhanced with the increase in the salt concentration, as shown in Figure 4D,E. The formed granular polyelectrolyte aggregates detected on the surface can be attributed to the salt-dependent self-assembly (a "saltingout" effect 49 ) under strengthened salinity, but little effect on the surface superoleophobicity was found. Next, to carry out a new force measurement, the washout experiment was repeated and equilibrated for 20 min.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, from the topographic images acquired by AFM surface imaging, it was found that the granular sensation of the surface is enhanced with the increase in the salt concentration, as shown in Figure 4D,E. The formed granular polyelectrolyte aggregates detected on the surface can be attributed to the salt-dependent self-assembly (a "saltingout" effect 49 ) under strengthened salinity, but little effect on the surface superoleophobicity was found. Next, to carry out a new force measurement, the washout experiment was repeated and equilibrated for 20 min.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The materials (oil, deionized water, silicon wafer) used for experiments were consistent with those used in our previous study. 49 Prior to all experiments, silicon wafers were cleaned via immersion in Piranha solution (1:3 (v/v) mixture of 30% H 2 O 2 and 98% H 2 SO 4 ), followed by heating until no bubbles were released to remove possible surface contaminants. The cleaned silicon wafers were rinsed with water and dried with nitrogen.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study has been facilitated by the advent of the atomic force microscope (AFM) (Binnig et al 1986), which permits the direct force measurement of interactions between homoand hetero-bodies within nano-Newton scale (Mate et al 1989;Snyder et al 1997;Aston and Berg 2002;Malotky and Chaudhury 2001). Moreover, the development of probe modification technique has promoted the exploration of interactions between deformable droplets/bubbles and solid surfaces (Dagastine et al 2004a(Dagastine et al , 2006Gunning et al 2004;Vakarelski et al 2010a;Balasuriya and Dagastine 2012;Tabor et al 2011a, b;Wang et al 2015;Jin et al 2017;Shi et al 2017). One interesting study applied the drop probe AFM technique to elucidate the intrinsic wetting mechanism of polyelectrolyte surfaces with varied hydrophobicity.…”
Section: Introductionmentioning
confidence: 99%